Open Dialogue services around the world: a scoping survey exploring organizational characteristics in the implementation of the Open Dialogue approach in mental health services - Pocobello, Raffaella; Camilli, Francesca; Alvarez-Monjaras, Mauricio; Bergström, Tomi; von Peter, Sebastian; Hopfenbeck, Mark; Aderhold, Volkmar; Pilling, Stephen; Seikkula, Jaakko; el Sehity, Tarek Josef (Frontiers in Psychology, 2023)
Objective: This cross-sectional study investigates the characteristics and practices of mental health care services implementing Open Dialogue (OD) globally. Methods: A structured questionnaire including a self-assessment scale to measure teams’ adherence to Open Dialogue principles was developed. Data were collected from OD teams in various countries. Confirmatory Composite Analysis was employed to assess the validity and reliability of the OD self-assessment measurement. Partial Least Square multiple regression analysis was used to explore characteristics and practices which represent facilitating and hindering factors in OD implementation. Results: The survey revealed steady growth in the number of OD services worldwide, with 142 teams across 24 countries by 2022, primarily located in Europe. Referrals predominantly came from general practitioners, hospitals, and self-referrals. A wide range of diagnostic profiles was treated with OD, with psychotic disorders being the most common. OD teams comprised professionals from diverse backgrounds with varying levels of OD training. Factors positively associated with OD self-assessment included a high percentage of staff with OD training, periodic supervisions, research capacity, multi-professional teams, self-referrals, outpatient services, younger client groups, and the involvement of experts by experience in periodic supervision. Conclusion: The findings provide valuable insights into the characteristics and practices of OD teams globally, highlighting the need for increased training opportunities, supervision, and research engagement. Future research should follow the development of OD implementation over time, complement self-assessment with rigorous observations and external evaluations, focus on involving different stakeholders in the OD-self-assessment and investigate the long-term outcomes of OD in different contexts.